EFFECTIVENESS ENSURING OF PRIVATE MEDICAL INSTITUTIONS - КUKLINOVA TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The paper presents the results of study of the efficiency of Ukrainian private healthcare systems. The article is devoted to health care development idea. Many countries are facing serious problems in health care sector. This study illustrates an effectiveness concerning the private healthcare systems in Ukraine. The object of research is process of effective development of private medical institutions. The specificity of health care analyzed in Ukraine. The paper deals with essential problems of the specific activity of private medical institutions in Ukraine. Main advantages and problems for applying the benchmarking private health care sector are defined. The effective private medical services to the population in conditions of aggravation of crisis phenomena has been shown in the presented work. The investment attractiveness of the private healthcare sector in Ukraine has been shown. The study deals with private medical institutions complex characteristic. The paper shows the importance of improving the efficiency of private medical institutions. The key aspects of their functioning are analyzed on the basis of a detailed analysis of the problems. Ukraine need to implement healthcare reforms. The main legal, organizational and socio-economic trends and features of the process of functioning of private medical institutions in Ukraine have been revealed in the study. The results of successful introduction of these proposals on the private medical institution of Ukraine are described. The mechanism of private medicine performance management is presented in this article. Proposals for providing steady growth of private healthcare systems in Ukraine has been adduced. Recommendations for ensuring the effective functioning of private medical institutions in Ukraine are developed.